2022
DOI: 10.1038/s41746-022-00643-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and characterising sources of variability in digital outcome measures in Parkinson’s disease

Abstract: Smartphones and wearables are widely recognised as the foundation for novel Digital Health Technologies (DHTs) for the clinical assessment of Parkinson’s disease. Yet, only limited progress has been made towards their regulatory acceptability as effective drug development tools. A key barrier in achieving this goal relates to the influence of a wide range of sources of variability (SoVs) introduced by measurement processes incorporating DHTs, on their ability to detect relevant changes to PD. This paper introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A second problem of the single digital biomarker hypothesis is the vulnerability of motor‐centric digital measures to confounding variables (Fig. 1C) and other sources of variation 16 . Here, systematic changes in a digital measurement are caused by unmeasured confounds rather than the neural dysfunction of Parkinson's disease.…”
Section: Digital Measures Can Be Confoundedmentioning
confidence: 99%
See 3 more Smart Citations
“…A second problem of the single digital biomarker hypothesis is the vulnerability of motor‐centric digital measures to confounding variables (Fig. 1C) and other sources of variation 16 . Here, systematic changes in a digital measurement are caused by unmeasured confounds rather than the neural dysfunction of Parkinson's disease.…”
Section: Digital Measures Can Be Confoundedmentioning
confidence: 99%
“…Walking carefully on an icy pavement could be misinterpreted as bradykinesia. Many aspects of human life unrelated to the neural dysfunction of Parkinson's disease will interact in unknown ways with digital measurement 16 . Active task‐based measures—where the patient is performing a particular task such as tapping a smartphone screen —provide some level of control against unmeasured environmental confounds, but are still susceptible to another kind.…”
Section: Digital Measures Can Be Confoundedmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, integration of features is likely necessary to enhance performance in longitudinal measurements. Combining multiple feature modalities allows for better separation of true effects from noise, improves individual‐level specificity, and mitigates bias and confounding 4 . A recent PD trial demonstrated a tendency toward effects on a longitudinal digital composite score consisting of multiple active and passive features, but not on gold standard clinical assessment 5 .…”
mentioning
confidence: 99%